EVALUATING THE EFFECTIVENESS OF GOVERNMENT ENTREPRENEURSHIP ASSISTANCE PROGRAMS ON MSME DEVELOPMENT IN LHOKSEUMAWE - Sari Yulis Terfiadi; Muttaqien; Likdanawati; Ishak Samusi; Farid Haikal (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to evaluate the effectiveness of government entrepreneurship mentoring programs on the development of MSMEs in Lhokseumawe City. Using a mixed-methods approach (quantitative and qualitative), the research analyzes the program’s impact on business performance, managerial capacity, and technology adoption among MSME actors. Data were collected through questionnaires, in-depth interviews, and document analysis, involving MSME participants, facilitators, and implementing institutions. The analysis focuses on assessing the program’s influence on key business development indicators, such as revenue growth, market expansion, managerial improvement, and digital technology adoption. The expected outcomes include measuring the level of program effectiveness, identifying implementation challenges, and evaluating its contribution to MSME growth. The findings are expected to provide policy recommendations and enrich the literature on entrepreneurship and evidence-based public policy. The main outputs of this study are a publication in a Sinta-3 accredited journal and an intellectual property right (HKI).